KETAHANAN MEDANG (Cinnamomum porrectum (Roxb.)DAN CEMARA GUNUNG (Casuarina junghuniana) TERHADAP KONSENTRASI MERCURI PADA MEDIA TAILING DENGAN INOKULASI FUNGI MIKORIZA ARBUSKULA (FMA) - Ahwal, Khoirotul; Muin, Abdurrani; Wulandari, Reine Suci (JURNAL HUTAN LESTARI, 2014)
This study aims to determine the endurance of cemara gunung (Casuarina junghuniana) and medang (Cinnamomum porrectum) toward mercury toxicity in tailings media and to determine the level of resistance and the cemara gunung and medang after AMF inoculated against mercury toxicity in tailings media .The study was conducted in green house Ex - situ Conservation and Development Research Institute of the University of Natural Orchid Tanjungpura Pontianak and silviculture in the Laboratory of the Faculty of Forestry, University of Tanjungpura. The research was using split-split plot design and each treatment was repeated 3 times. The treatment consists of : the main plot (the Cinnamomum porrectum (Roxb) and Casuarina junghuniana), as a subplot (without mycorrhizal inoculation and inoculated by 25 g mycorrhiza . As sub-sub plot (without Hg, 10 ppm HgCl2, 20 ppm HgCl2, Hg30 HgCl2 30 ppm, and HgCl2 40 ppm parameters observed were : the level of resistance against the mountain pine medang and mercury concentrations, the effect of AMF inoculation on plant resistance in mercury concentration, dry weight of roots and canopy, root shoot ratio, Hg measurement of root and canopy. Results of analysis of variance and the level of plant resistance Cinnamomum porrectum (Roxb) and Casuarina junghuniana mercury concentrations in some significant effect on endurance Cinnamomum porrectum (Roxb) and Casuarina junghuniana. This is evident in the type Cinnamomum porrectum (Roxb) with 40 ppm Hg concentrations showed symptoms of poisoning fastest . While the results of analysis of variance on the type Cinnamomum porrectum (Roxb) AMF inoculation and Casuarina junghuniana as well as its interaction with mercury no significant effect on plant resistance . Keywords : Cinnamomum porrectum (Roxb) Casuarina junghuniana, mercury, arbuscular mycorrhizae fungi and tailings